Pan-Cancer Analysis Identifies Liver Metastases as Negative Predictive Factor for Immune Checkpoint Inhibitors Treatment Outcome - Chen, Xiao-Juan; Ren, Aiqun; Zheng, Liang; Zheng, En-Dian; Jiang, Tao (Frontiers in Immunology, 2021)
This study aimed to investigate the predictive value of liver metastases (LM) in patients with various advanced cancers received immune-checkpoint inhibitors (ICIs). This study included three cohort. First, clinical and survival data from a published cohort of 1661 patients received ICIs therapy were downloaded and analyzed. Second, a retrospective review of 182 patients with advanced NSCLC received PD-1/PD-L1 monotherapy were identified. Third, a meta-analysis of published trials was performed to explore the impact of LM on the efficacy of anti-PD-1/PD-L1 based therapy in advanced lung cancers. Pan-cancer analysis revealed that patients with LM had significantly shorter overall survival (OS) than those without LM (10 vs. 20 months; P < 0.0001). Subgroup analysis showed that the presence of LM was associated with markedly shorter OS than those without LM (P < 0.0001) in ICI monotherapy group, while it did not reach the statistical significance in ICI-based combination therapy (P = 0.0815). In NSCLC, the presence of LM was associated with significantly inferior treatment outcomes in both the pan-cancer and real-world cohort. Interestingly, ICI-based monotherapy and combination therapy could simultaneously prolong progression-free survival (PFS) and OS in patients without LM. However, ICI-based monotherapy could not prolong PFS than chemotherapy in patients with LM while ICI-based combination therapy could dramatically prolong both PFS and OS. The current study suggested that the presence of LM was the negative predictive factor in cancer patients received ICIs monotherapy. ICI-based combination therapy might overcome the intrinsic resistance of LM to ICIs while the optimal combinatorial strategies remains further investigation.